2020
DOI: 10.1097/md.0000000000021231
|View full text |Cite
|
Sign up to set email alerts
|

Combining the tumor abnormal protein test with tests for carcinoembryonic antigens, cancer antigen 15–3, and/or cancer antigen 125 significantly increased their diagnostic sensitivity for breast cancer

Abstract: Background: The tumor abnormal protein (TAP) test is used to screen for many cancers, but its use for breast cancer has not been studied. Methods: Tests for carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), cancer antigen 15-3 (CA15-3), and TAP were administered to 261 women with operable benign breast disease and 348 with breast cancer. The cutoff value used for TAP was the mean + 3 standard deviations for benign breast disease patients (275.64 μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Many recent studies have demonstrated the sensitivity and specificity of TAP for the early screening, diagnosis, and prognosis of tumors. [8][9][10][11] In this study, we collected peripheral blood samples from 95 patients with gastric adenocarcinoma and 34 nontumor patients and evaluated the influence of TAP expression on screening diagnosis based on these samples. The positive rate of TAP in patients with gastric adenocarcinoma (68.4%) was significantly higher than that in nontumor patients (23.5%), indicating that TAP is more sensitive to gastric cancer; in other words, TAP can be used to monitor gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have demonstrated the sensitivity and specificity of TAP for the early screening, diagnosis, and prognosis of tumors. [8][9][10][11] In this study, we collected peripheral blood samples from 95 patients with gastric adenocarcinoma and 34 nontumor patients and evaluated the influence of TAP expression on screening diagnosis based on these samples. The positive rate of TAP in patients with gastric adenocarcinoma (68.4%) was significantly higher than that in nontumor patients (23.5%), indicating that TAP is more sensitive to gastric cancer; in other words, TAP can be used to monitor gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in veterinary medicine, it has also proven that clinically healthy dogs can be distinguished from those with mammary neoplasia by CA15-3 level 7 . Although the CA15-3 is considered to possess the advantage of high specificity to detect precursors of breast cancer, single CA15-3 detection has a high rate of missing in malignant breast tumors, especially in early tumor patients 8 . Therefore, to meet clinical needs, CA15-3 should be combined with other TM to assist in the diagnosis of breast cancer and metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The common markers used for diagnosis and monitoring of malignant tumors include carcinoembryonic antigen (CEA), carbohydrate antigen (CA)19‐9, and CA125 6–8 . Recent studies have shown that inflammatory responses play a crucial role in the occurrence and development of malignant tumors 9 .…”
Section: Introductionmentioning
confidence: 99%